Community Challenges in Accessing Educational Facilities - Mustakim, Marsuq (Moccasin Journal De Public Perspective, 2024)
This study aims to examine the key barriers affecting access to educational facilities in Moyo Island, West Nusa Tenggara, Indonesia, and to provide an integrated understanding of how these challenges influence educational inequality in remote island contexts.A qualitative case study approach was employed using semi-structured interviews with 30 participants, including parents, teachers, and community leaders. Data were analyzed using thematic analysis to identify major patterns and relationships among barriers. The findings reveal four primary barriers: geographical constraints, infrastructural deficiencies, economic limitations, and teacher shortages. These factors operate in an interconnected manner, where geographic isolation reduces school attendance, poor infrastructure creates unfavorable learning environments, economic pressures increase dropout risks, and teacher shortages lower educational quality. The study demonstrates that educational access in remote areas is shaped by a systemic interaction of multiple barriers. Therefore, integrated and multi-sectoral policy interventions are required to improve equitable access to education in rural and isolated communities.